Quantifying structural controls on fluid flow: Insights from carbonate-hosted fault damage zones on the Maltese Islands. (August 2017) - Dimmen, Vilde; Rotevatn, Atle; Peacock, David C.P.; Nixon, Casey W.; Nærland, Kari
Abstract: Structural complexity along faults (e.g., relay zones, fault intersections and jogs) exert strong controls on fluid flow, yet few attempts have been made to quantify and visualise such relationships. This paper does that using an outcrop-based study of fracture networks in carbonate rocks in Malta. We investigate the spatial distribution of low-porosity cemented mounds within the fracture networks, and the geometry and topology of the fracture networks are characterised. The mounds are associated with low porosity due to selective cementation along the faults, as well as with peaks in connecting node frequency (a topological proxy for network connectivity), and fracture intensity (a fracture abundance proxy for network complexity). Considering the mounds as a record of palaeo-fluid flow and palaeo-fluid-rock-interaction, this work therefore quantifies and visualises the relationship between structural complexity and fluid flow. Highlights: We quantify and visualise relationships between structural complexity and fluid flow. Outcrop examples of small-scale fault damage zones in carbonate rocks in Malta are used. Topology is used to quantify and spatially map network complexity and connectivity. Evidence of palaeo fluid flow spatially coincides with areas of high structural complexity. Quantification of structural complexity will improve prediction of fluid flow.